Microwave plasma formation within a 2D photonic crystal. (21st March 2017) - Parsons, Stephen; Gregório, José; Hopwood, Jeffrey
Abstract: Experiments demonstrate that an electromagnetic wave incident on a photonic crystal (PhC) containing a single point-defect causes gas breakdown. After breakdown we report the formation of a stable microwave plasma within this free-space vacancy. We show that gas breakdown is possible in low-pressure argon (10 Torr) using as little as 1.4 W of microwave power if the frequency of the incident wave is equal to the resonance of the vacancy (8.614 GHz). During formation, the plasma-filled defect decreases the transmission of energy through the photonic crystal by approximately two orders of magnitude. Plasma formation time is measured to be as fast as 100 ns at relatively high power (9 W). Using the transmission of energy through the PhC as a diagnostic tool, we report that the electron density of the microwave plasma is 10 16 –10 17 m −3 for argon pressures between 10 and 50 Torr. Finally, we consider the application of the self-initiated plasma within the PhC as a simple power limiter.